2017
DOI: 10.1002/cbf.3305
|View full text |Cite
|
Sign up to set email alerts
|

Lin28a enhances in vitro osteoblastic differentiation of human periosteum‐derived cells

Abstract: Despite a capacity for proliferation and an ability to differentiate into multiple cell types, in long-term culture and with ageing, stem cells show a reduction in growth, display a decrease in differentiation potential, and enter senescence without evidence of transformation. The Lin28a gene encodes an RNA-binding protein that plays a role in regulating stem cell activity, including self-renewal and differentiation propensity. However, the effect of the Lin28a gene on cultured human osteoprecursor cells is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…LIN28 is highly expressed in placenta and plays an important role in embryonic development and implantation as an RNA-binding protein 8 . Some studies have shown that the increase in LIN28B expression is positively correlated with the invasion, migration, and proliferation of trophoblast cells 19,20,30,31 . Can eld et al 8 found that invasive interstitial EVT expressed higher levels of LIN28B in placental sections during early pregnancy compared with non-invasive proximal trophoblast cells, and increased expression of LIN28B increased HTR8/SVneo cell proliferation, migration, and invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIN28 is highly expressed in placenta and plays an important role in embryonic development and implantation as an RNA-binding protein 8 . Some studies have shown that the increase in LIN28B expression is positively correlated with the invasion, migration, and proliferation of trophoblast cells 19,20,30,31 . Can eld et al 8 found that invasive interstitial EVT expressed higher levels of LIN28B in placental sections during early pregnancy compared with non-invasive proximal trophoblast cells, and increased expression of LIN28B increased HTR8/SVneo cell proliferation, migration, and invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that LIN28 plays a role in regulating stem cell activity, including self-renewal and differentiation. Therefore, during the early stages of embryonic development, early gene expression in the placenta is high, and cells continuously develop and differentiate 30,31 . LIN28 is also a key factor in the regulation of developmental differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that LIN28 plays a role in regulating stem cell activity, including selfrenewal and differentiation. Therefore, during the early stages of embryonic development, early gene expression in the placenta is high, and cells continuously develop and differentiate 30,31 . LIN28 is also a key factor in the regulation of developmental differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…LIN28 is highly expressed in placenta and plays an important role in embryonic development and implantation as an RNA-binding protein 8 . Some studies have shown that the increase in LIN28B expression is positively correlated with the invasion, migration, and proliferation of trophoblast cells 19,20,30,31 . Canfield et al 8 found that invasive interstitial EVT expressed higher levels of LIN28B in placental sections during early pregnancy compared with noninvasive proximal trophoblast cells, and increased expression of LIN28B increased HTR8/SVneo cell proliferation, migration, and invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%